2018
DOI: 10.1097/anc.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Practice Patterns Reported by Neonatologists and Neonatal Nurse Practitioners in the United States

Abstract: Future Research is needed to target aspects of practice where practice variations exist, or practice is not supported by evidence. Significant practice differences related to the device types should be considered in future research design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We received two comments by the survey responders that they would use a threshold FiO 2 of 30% while on humidified high flow nasal cannula (HHFNC) therapy. Recent surveys have found extensive use of HHFNC in special care nurseries in many parts of the world 32,33 . A recent large RCT concluded that HHFNC was not non‐inferior to CPAP and resulted in a higher incidence of treatment failure than CPAP when used as early respiratory support for preterm infants (>31 weeks) 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We received two comments by the survey responders that they would use a threshold FiO 2 of 30% while on humidified high flow nasal cannula (HHFNC) therapy. Recent surveys have found extensive use of HHFNC in special care nurseries in many parts of the world 32,33 . A recent large RCT concluded that HHFNC was not non‐inferior to CPAP and resulted in a higher incidence of treatment failure than CPAP when used as early respiratory support for preterm infants (>31 weeks) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys have found extensive use of HHFNC in special care nurseries in many parts of the world. 32,33 A recent large RCT concluded that HHFNC was not non-inferior to CPAP and resulted in a higher incidence of treatment failure than CPAP when used as early respiratory support for preterm infants (>31 weeks). 34 Another RCT concluded that HHFNC is inferior to CPAP as a primary noninvasive respiratory support in preterm infants (≥28 weeks) with respiratory distress.…”
Section: Nomentioning
confidence: 99%
“…High‐flow nasal cannula (HFNC) oxygen therapy has been a popular type of noninvasive respiratory support, widely used in NICUs because it is comfortable, easy to setup, and has a low incidence of nasal trauma 7–13 . There is an increasing number of studies on the advantages, indications, and risks of using HFNC in neonates, as well as comparing its effectiveness with that of NCPAP and other noninvasive ventilation modes.…”
Section: Introductionmentioning
confidence: 99%
“…High-flow nasal cannula (HFNC) oxygen therapy has been a popular type of noninvasive respiratory support, widely used in NICUs because it is comfortable, easy to setup, and has a low incidence of nasal trauma. [7][8][9][10][11][12][13] There is an increasing number of studies on the advantages, indications, and risks of using HFNC in neonates, as well as comparing its effectiveness with that of NCPAP and other noninvasive ventilation modes. However, uncertainty surrounding the use of HFNC in the NICU remains, and cultural differences in China regarding the preferences and values of Chinese parents bring up the necessity to develop HFNC guidelines that consider Chinese culture.…”
mentioning
confidence: 99%
“…However, CPAP has high skill requirements for nurses as the improper use would lead to adverse outcomes including nasal mucosal injury or necrosis, nasal granuloma, nasal vestibular stenosis, and nasal septum deformation or deletion in infants, and the special caps that needs to be worn for fixation to ensure ventilation effect would add discomfort for infants (2,5,6). High-flow Nasal Cannula Oxygen Therapy (HFNC), also known as Heated Humidified High Flow Nasal Cannula (HHHFNC), is a newly emerged non-invasive respiratory support technology and has been increasingly applied in NICU as an alternative to CPAP (1,(7)(8)(9)(10)(11)(12)(13). Compared with CPAP, HFNC has several merits in promoting alveolar dilation (14)(15)(16)(17)(18), improving gas exchange (14,19), protecting airway mucosa (20), and reducing respiratory work (19).…”
Section: Introductionmentioning
confidence: 99%